1982
DOI: 10.1177/001872088202400607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Video Display Terminals on Telephone Operators

Abstract: A self-administered questionnaire was completed by 145 Directory Assistance operators who used video display terminals (VDTs) to retrieve listings and by 105 control subjects who performed identical work except that they retrieved listings from printed paper records. The two groups exhibited few differences in their experience of work-related physical discomfort, in job satisfaction, or in their concerns about job security. Both groups were found to use eyeglasses and contact lenses to the same extent. VDT ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 2 publications
0
16
0
1
Order By: Relevance
“…Several studies have found a higher prevalenc e of eye discomfort or asthenopia among VDT operators compared with non-VDT operators, or a prevalence that increa sed with VDT working time (15)(16)(17)(18)(19)(20). Other studies have failed to do so (5, 2 1, 22), although a nonsignifi cant increase was seen at least in one study (22). In a few N = 191).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies have found a higher prevalenc e of eye discomfort or asthenopia among VDT operators compared with non-VDT operators, or a prevalence that increa sed with VDT working time (15)(16)(17)(18)(19)(20). Other studies have failed to do so (5, 2 1, 22), although a nonsignifi cant increase was seen at least in one study (22). In a few N = 191).…”
Section: Discussionmentioning
confidence: 91%
“…Belisario et al (15), on the other hand, failed to find associations between redness or sensitivity to light and VDT work. Teariness or itching was not significantly associated with VDT work or VDT work duration (15,18,22). Coe et al [cited from Collins et al ( 16)] found an increase in the reporting of aches among VDT operators compared with that of referen ts.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between VDT and non-VDT users as to muscle problem prevalences have yielded varied results (Fahrbach and Chapman 1990, Hagberg and Wegman 1987, HUnting et al 1981, Laubli and Grandjean 1984, Rossignol et al 1987, Sauter 1984, Smith et al 1981, Starr et al 1982, Van der Heiden et al 1984, probably due to inhomogeneity of the VDT user group, and possibly also due to variations in the comparison groups (Laubli and Grandjean 1984). Comparisons between studies are also hampered by the frequent lack of adequate descriptions of the effect, and the paucity (in many studies) of information on the prevalence of other relevant factors.…”
Section: Is Vdt Use Related To Increased Occurrence Of Muscle Problems?mentioning
confidence: 99%
“…This is compatible with previous studies reporting that pain in the neck and shoulder was the Table 6. Odds ratios (95% confidence intervals) of variables for MSDs in the upper extremity areas estimated by multiple logistic analyses most prevalent musculoskeletal symptom in VDT workers (1,21,22). Many studies have addressed the effect of job stress on MSDs in the upper extremities (8,(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%